The Organizational Context for Teaching and Learning. A Review of the Research Literature - Peterson, Marvin W.; National Center for Research to Improve Postsecondary Teaching and Learning, Ann Arbor, MI. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
Three broad categories are cited that describe the nature of a college or university as an organization and that potentially influence an institutions academic outcomes. These categories are: the college's formal organizational characteristics, structures, processes, and practices; its culture; and its climate. This literature review aims to identify and clarify concepts related to this framework, identify organizational characteristics related to improvement of student outcomes, and refine the research framework. The review is divided into the following sections: (1) performance measures in higher education: effectiveness, efficiency, quality, and student outcomes; (2) organizational culture and climate: an external perspective; (3) defining culture and climate in higher education: conceptual confusion; (4) institutional strategy and student outcomes; (5) academic management practices: impacts on culture, climate, and student outcomes; (6) organizational characteristics: relationships to culture, climate and outcomes; (7) overview of organizational variables, practices, and characteristics; and (8) a conceptual synthesis: complexity or chaos. Both higher education and non-higher education literature is included. Five hundred and sixty-five references are included. (LB)
Availability: NCRIPTAL, Suite 2400 School of Education Building, The University of Michigan, Ann Arbor, MI 48109-2748 (Technical Report No. 86-E-001.0, $10.00).
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: OERI-86-0010.
ERIC Note: From the NCRIPTAL Program on the Organizational Context for Teaching and Learning.
Microfiche.
Keywords: Cognitive Psychology; Educational Research; College Outcomes Assessment